INTEGRATION OF GREEN OPEN SPACES IN TOURISM ACCOMMODATION GLAMPING RICHLAND BATURITI BALI - Kerdiati, Ni Luh Kadek Resi (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2024)
Glamping tourism is currently experiencing rapid growth. This is because this type of tourism offers a unique natural tourism experience with modern and comfortable facilities. This research focuses on green open spaces at Richland Glamping Baturiti Bali. Richland Glamping Baturiti is a glamping accommodation that provides green open space in an area with beautiful natural beauty. This allows the development of optimal green open spaces harmoniously with the surrounding environment. Hopefully, this research can contribute to realizing glamping tourism, which provides a unique and exciting tourist experience, preserves nature and supports sustainable development. This research uses qualitative methods with the object of the Richland glamping case study in Bali, which has green open spaces. Primary data was collected through observation and documentation, while secondary data was obtained from the library. All information and data are analyzed using relevant theories and then explained descriptively. Glamping offers luxury accommodations in nature with a commitment to cleanliness and personal service. The green open space is designed with ecological principles to improve the quality of life, groundwater, and ecosystem balance. Through these environmental design principles, an analysis was carried out on the case objects of green open space at Glamping Richland Bali. The Richland Glamping Baturiti Bali case study shows how this principle can be applied by choosing the right plants and location, creating a harmonious and environmentally friendly experience for visitors.